Three ammonium salts of sulfathiazole: crystallography and anti-microbial assay - Akhmad Aznan, Aina Mardia; Abdullah, Zanariah; Khoo, Chai Hoon; Chen, Bao Jing; See, Tian Hong; Sim, Jiun Horng; Cheah, Yoke Kqueen; Seng, Hoi Ling; Tiekink, Edward R.T. (Walter de Gruyter GmbH, 2015)
The crystal and molecular structures of three ammonium salts derived from sulfathiazole are described. In each case, the anion is in the azanide form, features an intramolecular S←O interaction, and adopts a U-shape. The structures of two cations, [R(HOCH2CH2)NH2]+, namely for R = Me (1) and iPr (2), are unprecedented in the crystallographic literature. Extensive hydrogen bonding is observed in all crystal structures and leads to a two-dimensional array for 1, and three-dimensional architectures for each of 2 and 3 (R = CH2CH2OH). The salts exhibited anti-microbial activity against a range of Gram-positive and Gram-negative bacteria, and proved bactericidal toward Vibrio parahaemolyticus, but had no advantage over sulfathiazole itself.